Soil amendments influence early plant survival and growth in reclamation of severely degraded lands by gold mining in the Peruvian Amazon - Herrera-Machaca, Marx; Ancco-Mamani, Carlos; Alarcon Aguirre, Gabriel; Gonzales-Alvarado, Antony Cristhian; Garate-Quispe, Jorge Santiago (Brawijaya University, 2024)
Gold mining has been causing the most severe impacts on the soils of the Peruvian Amazon. It has created challenges for their recovery. In this context, soil amendments could play a crucial role in plant establishment in post-mining soils. The study aimed to analyze the effects of two amendments on the early plant survival and growth of seven species in the reclamation of severely degraded lands by gold mining in the Southeastern Peruvian Amazon. The study was based on a completely randomized block design, including 2-amendment treatments (T1: sawdust + island guano manure and T2: T1 + organic soil + hydrogel) and a control. The plant survivorship, height growth, diameter growth, and biomass accumulation were measured. This study found that amendments may be effective at increasing survivorship and plant growth in degraded lands by gold mining in the Peruvian Amazon. The amendments increased the survival, diameter, height, and biomass of most plant species in the study. In general, survivorship and plant growth in T2 were high compared to T1. At the end of the experiment, the highest survivorship was for an Indigofera suffruticosa and Crotalaria pallida (>80%). The diameter growth was higher in T2 than in T1. The species growing fastest in diameter (>1.5 cm) were Crotalaria cajanifolia, C. pallida and Ochroma pyramidale. Soil amendments provided similar effects on height for most species except for I. suffruticosa. Therefore, C. pallida, I. suffruticosa, C. cajanifolia and O. pyramidale are key species to be considered in reforestation and/or restoration initiatives, due to its potential to acclimate and establish itself in severely degraded areas.